2022
DOI: 10.1039/d2lc00098a
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming microfluidic microbial fuel cells: a biocompatible membrane grown in situ improves performance and versatility

Abstract: Recent trends in microfluidic microbial fuel cells (MFCs) is to exclude a separation membrane, instead relying on the physics of laminar flow to maintain isolation between anode and cathode compartments....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…After 75 days of total operation (approximately one month under the R ext = 15 kΩ external load), the continuous power at Q T = 1.0 mL h −1 had increased to 2.47 W m −2 . This value is significantly higher than that from the previously highest performing microfluidic MFC containing a pure-culture G. sulfurreducens EAB 25 and matched the highest reported power density from the best performing graphite-electrode microfluidic MFC (2.45 W m −2 ), even though the previous work used higher flow rates ( Q T = 20 mL h −1 ) and a mixed species–species (EAB). 5 We refer the reader to previous work where a mature biofilm was imaged by scanning electron microscopy after 6 months in an unmodified membraneless MFC.…”
Section: Resultssupporting
confidence: 67%
“…After 75 days of total operation (approximately one month under the R ext = 15 kΩ external load), the continuous power at Q T = 1.0 mL h −1 had increased to 2.47 W m −2 . This value is significantly higher than that from the previously highest performing microfluidic MFC containing a pure-culture G. sulfurreducens EAB 25 and matched the highest reported power density from the best performing graphite-electrode microfluidic MFC (2.45 W m −2 ), even though the previous work used higher flow rates ( Q T = 20 mL h −1 ) and a mixed species–species (EAB). 5 We refer the reader to previous work where a mature biofilm was imaged by scanning electron microscopy after 6 months in an unmodified membraneless MFC.…”
Section: Resultssupporting
confidence: 67%
“…After 75 days of total operation (approximately one month under the Rext=15 kΩ external load), the continuous power at QT=1.0 mL h -1 had increased to 2.47 W m -2 . This value is significantly higher than that from the previously highest performing microfluidic MFC containing a pure-culture G. sulfurreducens EAB 25 and matched the highest reported power density from the best performing graphite-electrode microfluidic MFC (2.45 W m -2 ), even though the previous work used higher flow rates (QT=20 mL h -1 ) and a mixed species-species (EAB). 5 To test the upper limits of the output of our new design, we collected polarization curves under increasing flow rates.…”
Section: Performance Of a Modified Mfc After Maturationsupporting
confidence: 68%
“…The inverse relationship between PVCR and QT in opposition to areal power densities because improvements to raw power at high flow rates provide diminishing returns after de-acidification and mass transport are maximized. Considering that the results from a previous report were collected at a wider range of flow rates, 25 it is apparent that PVRC and IVCR improve at lower flow rates, in that case reaching PVCR=2.12 mW L -1 d (NER=0.051 kWh m -3 ) and Δ[Ac]=1.5 mM at QT=0.1 mL h -1 . We compared this previous PVCR value with that from the present study by extrapolation to QT=0.1 mL h -1 with an empirical fitting function (see Figure 6) and found that the VCR-normalized power in our study could have been as high as PVCR=8.71 mW L -1 d (NER=0.209 kWh m -3 ), which is close to the average value for larger acetatefed mixed-species MFCs, i.e., PVCR=10.42 mW L -1 (NER=0.250 kWh m -3 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We anticipate the incorporation of more micro-scale MFC features will be an avenue to future development. For now, fully microfluidic systems have been the subject of significant development as tools for better understand fundamental aspects of electroactive biofilms [ 74 , 290 , 291 , 292 ] as well as toward practical considerations including fine-tuning of electrode spacing, hydrodynamic effects, and the associated resistance distribution [ 293 , 294 , 295 , 296 ]. Moreover, it is anticipated that certain micro- and milli-fluidic elements can be integrated into otherwise large-scale MFC systems.…”
Section: Best Performing Substrates—a Path To Implementationmentioning
confidence: 99%